The staining ability of natural flower extracts as alternative dyes for bacterial staining - Cafoor, F.N.; Najeem, F.N.; Haseeb, H.F.; Thillainathan, K.; Sivasinthujah, S.; Gnanakarunyan, T. (University of Jaffna, 2024)
Gram staining is used as a routine stain in bacteriology. Synthetic stainsare commonly used for Gram staining which were reported to cause adverse effects to the environment and user. The use of natural dyes for microbial staining could be eco- friendly and non-toxic. As a result, plant-derived dyes are proposed as alternative stains for staining microorganisms.
Keywords: Staining; Thunbergia erecta; Clitoria ternatea; Simple staining; Gram staining